Evaluation of insect growth regulators, temephos and Bacillus thuringiensis israelensis against Aedes aegypti (L) in plastic containers - Lau, K.W.; Chen, C.D.; Lee, H.L.; Sofian-Azirun, Mohd (2015)
The residual activities of 5 insect growth regulators (IGRs) were studied and compared to operational dosage of temephos (1 mg/L) and Bacillus thuringiensis israelensis (Bti) (0.008 mg/L). The IGRs, temephos and Bti were applied into plastic containers containing 5 litres of water. Thirty Aedes aegypti larvae were added into each container weekly. Efficacy of these IGRs were evaluated for effective duration of each dosage and the percentage of emergence inhibition (EI). An end-point of EI/mortality >= 50% was considered to be effective. Pyriproxyfen possessed the longest residual activity in both indoor (43 weeks) and outdoor (26 weeks) conditions, followed by temephos (26 weeks in indoor and 16 weeks in outdoor). Although the residual activity of Bti in indoor lasted 8 weeks which was longer than cyromazine and diflubenzuron; however, it was least effective in outdoor which only lasted 2 weeks. This study revealed that pyriproxyfen possessed good residual effect among test IGRs compared to temephos and Bti. The use of IGRs can be an alternative long-term control measure in stagnant water body.